2021
DOI: 10.1002/anie.202110783
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Reaction of Propargyl Esters and Alkynylsilanes: Synthesis of Vinylallene Derivatives through a Twofold 1,2‐Rearrangement

Abstract: The reaction of propargyl esters with alkynylsilanes under gold catalysis provides vinylallene derivatives through consecutive [1,2]‐acyloxy/[1,2]‐silyl rearrangements. Good yields, full atom‐economy, broad substrate scope, easy scale‐up and low catalyst loadings are salient features of this novel transformation. Density Functional Theory (DFT) calculations suggest a reaction mechanism involving initial [1,2]‐acyloxy rearrangement to generate a gold vinylcarbene intermediate which upon regioselective attack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Thus, while aryl-substituted alkynylsilanes bearing electron-donating groups provided the expected cyclopentadienes in moderate to good yields, alkynylsilanes featuring aryl groups containing electron-withdrawing groups were found to be problematic, delivering the corresponding products in modest yields, even though these substituents were well-tolerated in Method A. The low performance of these alkynylsilanes in the cascade process is consistent with our previous study, 9 which showed that these alkynylsilanes exhibit much reduced reactivity in the formation of the required vinylallene intermediate.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Thus, while aryl-substituted alkynylsilanes bearing electron-donating groups provided the expected cyclopentadienes in moderate to good yields, alkynylsilanes featuring aryl groups containing electron-withdrawing groups were found to be problematic, delivering the corresponding products in modest yields, even though these substituents were well-tolerated in Method A. The low performance of these alkynylsilanes in the cascade process is consistent with our previous study, 9 which showed that these alkynylsilanes exhibit much reduced reactivity in the formation of the required vinylallene intermediate.…”
supporting
confidence: 88%
“…We have recently reported the gold-catalyzed reaction of propargylic esters 1 with alkynylsilanes 2 to provide silyl-substituted vinylallene derivatives 3 resulting from consecutive [1,2]-acyloxy/[1,2]-silyl rearrangements (Scheme B) . Notably, under the developed conditions, the formed vinylallenes did not evolve to the corresponding functionalized cyclopentadienes.…”
mentioning
confidence: 99%
“…The corresponding free energy barriers are 12.1 kcal/mol and 2.8 kcal/mol, respectively, indicating a rapid process. The consequence of stepwise acetoxy transfer is the formation of oxonium intermediate M3 , which could be regarded as an equilibrium with intermediate M1 in thermodynamic 74 76 . Resonance structure M3’ clearly reveals the electrophilicity of its terminal methylene position, which results in an intramolecular electrophilic 1,5-annulation via transition state TS3 to irreversibly form an Au-carbene complex M4 .…”
Section: Resultsmentioning
confidence: 99%